Algorithmic aspects of cloud computing : second International Workshop, ALGOCLOUD 2016, Aarhus, Denmark, August 22, 2016, Revised selected papers /: second International Workshop, ALGOCLOUD 2016, Aarhus, Denmark, August 22, 2016, Revised selected papers. (2017) - Unknown
No abstract available